2016
DOI: 10.18483/ijsci.957
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Copper Nanoparticles and Copper Nanocomposites against Escherichia Coli Bacteria

Abstract: Nanotechnology is an emerging technology which has wide applications in many fields. The major objective of the study is to synthesise copper nanoparticles and its composites and to determine their antibacterial activity. A filter based on the developed material was fabricated. Copper nanoparticles were synthesised by chemical reduction method and were encapsulated in a biopolymer, alginate and fabricated anti bacterial water filter using copper nanoparticle-coated polyurethane foams. The synthesised copper na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
0
12
0
3
Order By: Relevance
“…Immense research has been carried out on copper nanoparticles. They have been studied to exhibit deleterious effects on E. coli (Deryabin et al 2013;Jamshidi and Jahangiri-Rad 2014;Harikumar and Aravind 2016;Chatterjee et al 2014), Bacillus subtilis (Yoon et al 2007), Pseudomonas aeruginosa and Staphylococcus aureus (Azam et al 2012).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Immense research has been carried out on copper nanoparticles. They have been studied to exhibit deleterious effects on E. coli (Deryabin et al 2013;Jamshidi and Jahangiri-Rad 2014;Harikumar and Aravind 2016;Chatterjee et al 2014), Bacillus subtilis (Yoon et al 2007), Pseudomonas aeruginosa and Staphylococcus aureus (Azam et al 2012).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…An increase in the antibacterial effect related to the nanometal amount suggested that the diffusion of Ag and Cu ions from the nanocomposite was the main mechanism of the antimicrobial action of the powdery nanocomponents, while Ti 3 C 2 MXene and Al 2 O 3 nanoparticles played minor roles. The action of nano-Ag and nano-Cu is related to the adhesion of nanoparticles to the cell membrane and following interactions with its components resulting in changes of the cell permeability and affecting cellular respiration, enzymatic, gene expression, and metabolic processes [ 34 , 35 , 36 , 37 ]. The induction of oxidative stress associated with the generation of reactive oxygen species (ROS) and silver ion release should also be considered [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cu nanoparticles of magnolia leaf extract have been biologically synthesized to develop stable nanoparticles sized 40 to 100 nm. Furthermore, the activity of Cu nanoparticles has shown potential antibacterial activity against cells of Escherichia coli [32]. Syzygium aromaticum (clove) extracts have been used in the synthesis of Cu nanoparticles with a spherical to granular morphology and a mean particle size of 40 nm [33].…”
Section: Nanoparticles Synthesized From Plant Extractsmentioning
confidence: 99%